How Do Oysters Remove Nitrogen? - Heather Donnelly; Ashley Smyth; Shirley Baker; Laura Reynolds; Angela Collins (EDIS)
Nitrogen is natural and necessary, yet nitrogen levels above natural levels can cause algal blooms and eutrophication of coastal systems. The purpose of this document is to describe how oysters and oyster reefs remove nitrogen. This new 7-page publication of the UF/IFAS Department of Soil, Water, and Ecosystem Sciences is intended for policymakers, environmental organizations, and coastal residents who want to know about oysters' role in improving water quality through nitrogen removal. Written by Heather Donnelly, Ashley Smyth, Shirley Baker, Laura Reynolds, and Angela Collins. https://edis.ifas.ufl.edu/ss711